Impact of ≥ 0.1-mm free resection margins on local intramural residual cancer after local excision of T1 colorectal cancer - Gijsbers, Kim M.; van der Schee, Lisa; van Veen, Tessa; van Berkel, Annemarie M.; Boersma, Femke; Bronkhorst, Carolien M.; Didden, Paul D.; Haasnoot, Krijn J.C.; Jonker, Anne M.; Kessels, Koen; Knijn, Nikki; van Lijnschoten, Ineke; Mijnals, Clinton; Milne, Anya N.; Moll, Freek C.P.; Schrauwen, Ruud W.M.; Schreuder, Ramon-Michel; Seerden, Tom J.; Spanier, Marcel B.W.M.; Terhaar Sive Droste, Jochim S.; Witteveen, Emma; de Vos tot Nederveen Cappel, Wouter H.; Vleggaar, Frank P.; Laclé, Miangela M.; ter Borg, Frank; Moons, Leon M.G.; Dutch T1 CRC Working Group (Endoscopy International Open, 2022)
Background and study aims A free resection margin (FRM) > 1 mm after local excision of a T1 colorectal cancer (CRC) is known to be associated with a low risk of local intramural residual cancer (LIRC). The risk is unclear, however, for FRMs between 0.1 to 1 mm. This study evaluated the risk of LIRC after local excision of T1 CRC with FRMs between 0.1 and 1 mm in the absence of lymphovascular invasion (LVI), poor differentiation and high-grade tumor budding (Bd2–3).Patients and methods Data from all consecutive patients with local excision of T1 CRC between 2014 and 2017 were collected from 11 hospitals. Patients with a FRM ≥ 0.1 mm without LVI and poor differentiation were included. The main outcome was risk of LIRC (composite of residual cancer in the local excision scar in adjuvant resection specimens or local recurrence during follow-up). Tumor budding was also assessed for cases with a FRM between 0.1 and 1mm.Results A total of 171 patients with a FRM between 0.1 and 1 mm and 351 patients with a FRM > 1 mm were included. LIRC occurred in five patients (2.9 %; 95 % confidence interval [CI] 1.0–6.7 %) and two patients (0.6 %; 95 % CI 0.1–2.1 %), respectively. Assessment of tumor budding showed Bd2–3 in 80 % of cases with LIRC and in 16 % of control cases. Accordingly, in patients with a FRM between 0.1 and 1 mm without Bd2–3, LIRC was detected in one patient (0.8%; 95 % CI 0.1–4.4 %).Conclusions In this study, risks of LIRC were comparable for FRMs between 0.1 and 1 mm and > 1 mm in the absence of other histological risk factors.